Kualitas Papan Semen Partikel Kayu Mahang Quality Cement Board Particle Wood Mahang : Gimson Luhan, H.M. Damiri, John F. Gustaf - Admin JHT (HUTAN TROPIKA, 2016)
ABSTRACT Exploiting the potential and diversity of types of peat swamp forest is not known (lesser known species) both types of timber and non-timber forest products, needs to be done to anticipate the reduction in the availability of commercial timber is to alternatively manufacture of cement particle board. As an alternative building materials manufacture of particle board has good prospects, given the increasing need tehadap shelter each year. Selection of wood types mahang as many grown on peat swamp forest in Central Kalimantan and nature meet the criteria of wood as raw material for cement particle board and supported by the manufacturing process is quite easy. The study aims to determine the effect of particle size and the ratio of adhesive cement with wooden particles mahang against mechanical and physical properties of particles produced cement board, and can determine the quality of the cement particle boards that meet the requirements of building materials. Based on the terms of quality of cement board wood patikel mahang produced, including a group of cement particle board type III (> 0,6 g / cm3), medium density of 0,40 g/cm3 - 0,80 g/cm3, and including cement particle boards used for wall with a specific gravity of 0,70 to 0,90. Based on the terms of raw material utilization efficiency of wood mahang then recommended a combination treatment a1b1 (the weight ratio of the amount of cement with particles 1: 1,5 and small particle size) produces cement particle board that filled the finest wood standard. Research advanced mechanical properties of cement particle board of wood to meet the internal bond (kg/cm2) and a strong grasp of the screw (kg). Keywords: wood particle mahang, cement, physics and mechanical properties of cement particle board